« Gettiamo la semente comunista fra le donne proletarie » : Compagna et la révolution - Barbara Meazzi (Laboratoire Italien)
Compagna, a four-page, four-column magazine, first appeared in Rome on 5 March 1922. It was designed to be the platform of the central office of the Communist Party of Italy, a forum for use by women: workers, housewives, labourers and proletarians. It was, at least in the early days, a propaganda tool for the Communist revolution; it then, rather quickly, became a tool of anti-fascist resistance, before it ultimately disappeared. The editors were convinced that the transformation of the feminine condition was closely linked to that of the proletariat, following the example of the Russian Revolution. In this paper we will explore the contents of Compagna and analyse in greater detail the methods employed to educate women, sowing in them the seeds of revolution, as well as the idea of the connection between the resolution of the female problem and the victory of the proletariat. Our analysis will be limited to the period 1922-1925.